Pregnancy-related hypertension: a cardiovascular risk situation - Mounier-Vehier, Claire; Delsart, Pascal (La Presse médicale (1983), 2009)
Pregnancy-related hypertension is defined by systolic blood pressure > or = 140 mmHg and/or diastolic blood pressure > or = 90 mmHg at any term. It is more appropriate to talk about "hypertensive pregnancy syndromes", for the clinical aspects can be very heterogeneous. This disease is still common and affects approximately 10 to 15% of pregnancies. It essentially involves pathological placentation. When the maternal endothelium tolerates the trophoblast, the pregnancy is normal. Two elements play pivotal roles in the genesis of preeclampsia: defective placentation around 16 weeks of gestation and abnormal maternal response to placentation. Hypertension is difficult to diagnose during pregnancy because pregnant women are very subject to white coat hypertension. Self-monitoring and ambulatory monitoring of blood pressure are especially useful in this situation. Insofar as possible, it is important to distinguish preexisting hypertension, which preceded pregnancy, simple pregnancy-related hypertension, and more complicated forms, for their management differs. Treatment to lower blood pressure is aimed solely at preventing maternal complications of hypertension; lt has no effect on the course of the pregnancy and is sometimes even harmful for fetal growth. Except in cases of preeclampsia, it is not urgent to begin such treatment during pregnancy. If required, blood pressure should be reduced very progressively to maintain placental perfusion while slowly reaching a target value between 120/80 and 140/90 mmHg. Platelet aggregation inhibitors are the only effective preventive treatment for placental ischemia. They are reserved for at-risk pregnancies after 16 weeks of gestation, at a dose of 100mg/day. Short-term risks are associated especially with the complicated forms of hypertension. In the long term, preeclampsia is a marker of cardiovascular risk, for these women are at risk of developing chronic hypertension or having a cardiovascular accident in later years. Pregnancy is currently considered a situation that can reveal the likelihood of developing the metabolic syndrome and its cardiovascular complications.